Association Between Liquid Biopsy and Prognosis of Gastric Cancer Patients: A Systematic Review and Meta-Analysis - Gao, Yunhe; Xi, Hongqing; Wei, Bo; Cui, Jianxin; Zhang, Kecheng; Li, Hua; Cai, Aizhen; Shen, Weishen; Li, Jiyang; Rosell, Rafael; Chao, Joseph; Chen, Tianhui; et al. (Frontiers in Oncology, 2019)
Background: Reports regarding liquid biopsy and gastric cancer (GC) have emerged rapidly in recent decades, yet their prognostic value still remains controversial. This study was aimed to assess the impact of liquid biopsy, including circulating tumor cells (CTCs) and cell-free nucleic acids, on GC patients’ prognosis. Methods: Pubmed, Medline, EMBASE, or ClinicalTrial.gov databases were searched for studies that reporting GC patient survival data stratified by CTC/circulating tumor DNA(ctDNA)/circulating miRNAs’ status. The hazard ratios (HRs) and their 95% confidence intervals (CIs) for patients’ overall survival (OS) and disease-free survival (DFS)/progression-free survival (PFS) were recorded or calculated depending on circulating targets status. Results: We initially identified 4221 studies, from which 43 were eligible for further analysis, comprising 3814 GC patients. Pooled analyses showed that detection of certain CTCs, ctDNA and circulating miRNA, was associated with poorer overall survival (CTCs: HR=1.84, 95%CI 1.50-2.26, p<0.001; ctDNA: HR=1.78, 95%CI 1.36-2.34, p<0.001; circulating miRNA: HR=1.74, 95%CI 1.13-2.69, p<0.001) and disease-free survival/progression-free survival (CTCs: HR=3.39, 95%CI 2.21-5.20, p<0.001; ctDNA: HR=2.38, 95%CI 1.31-4.32, p=0.004; circulating miRNA: HR=3.30, 95%CI 2.39-4.55, p<0.001) of GC patients, regardless of disease stage and time point at which sample is taken (at baseline or post treatment). Conclusions: The presence of CTCs and/or cellular components identifies a group of GC with poorer prognosis. Among circulating markers, CTCs demonstrated a stronger and more stable predictive value for late-stage disease and among Mongolian populations with GC. Less data is available for ctDNA and miRNA, however, their presence may also reflect aggressive biology and warrants further prospective study.